A Cross-Layer-Based Clustered Multipath Routing with QoS-Aware Scheduling for Wireless Multimedia Sensor Networks. (30th May 2012) - Almalkawi, Islam T.; Guerrero Zapata, Manel; Al-Karaki, Jamal N.
Abstract : Wireless multimedia sensor networks (WMSNs) can handle different traffic classes of multimedia content (video, audio streams, and still images) as well as scalar data over the network. To ensure correct delivery of real-time multimedia data and efficient resource utilization, a proposed solution should provide both quality of service (QoS) assurance and energy efficiency. In this paper, we propose a cross-layer-based routing protocol that can utilize MAC-layer QoS-based scheduling for more efficient routing mechanism in WMSNs. Our proposed optimization is based on clustered multipath routing protocol and adaptive QoS-aware scheduling for the different traffic classes in WMSNs. Our design exploits the hierarchical structure of powerful cluster heads and the optimized multiple paths along with the adaptive scheduling to support reliable, high-throughput, and energy-efficient multimedia transmission in WMSNs. Simulation results show a significant performance improvement of our proposed design when compared to other similar routing schemes.